2020
DOI: 10.1038/s41588-019-0557-x
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive molecular characterization of mitochondrial genomes in human cancers

Abstract: Mitochondria are essential cellular organelles that play critical roles in cancer. Here, as part of the International Cancer Genome Consortium/The Cancer Genome Atlas Pan-Cancer Analysis of Whole Genomes Consortium, which aggregated whole-genome sequencing data from 2,658 cancers across 38 tumor types, we performed a multidimensional, integrated characterization of mitochondrial genomes and related RNA sequencing data. Our analysis presents the most definitive mutational landscape of mitochondrial genomes and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
379
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(423 citation statements)
references
References 57 publications
42
379
2
Order By: Relevance
“…encoded genes. The number of copies of mtDNA greatly affect the expression level of mitochondrial genes and this close association between mtDNA copy number and gene expression has been reported by Yuan et al (8) utilizing data from the International Cancer Genome Consortium and Reznik et al (11) using TCGA data. Additionally, certain host genes may also control mitochondrial gene expression (50).…”
Section: Overall Luad Lusc ------------------------------------------mentioning
confidence: 57%
See 1 more Smart Citation
“…encoded genes. The number of copies of mtDNA greatly affect the expression level of mitochondrial genes and this close association between mtDNA copy number and gene expression has been reported by Yuan et al (8) utilizing data from the International Cancer Genome Consortium and Reznik et al (11) using TCGA data. Additionally, certain host genes may also control mitochondrial gene expression (50).…”
Section: Overall Luad Lusc ------------------------------------------mentioning
confidence: 57%
“…Mitochondrial genome instability and impaired mitochondrial function are hallmarks of cancer progression (1)(2)(3). The somatic mutations and copy number variations in mitochondrial genomes have been frequently reported to be associated with the clinical stage of a tumor and notably affect the malignancy progression of lung cancer (4-7) and pan-adenocarcinoma (8). Furthermore, it has been demonstrated that a decrease in mitochondrial DNA (mtDNA) alters mitochondrial gene expression, resulting in a deficiency in oxidative phosphorylation, and this results in the disturbance of cellular functions (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the default settings, we further explored the impact of three extra ltering strategies on mtDNA mutation calling: lter 1 removes C > A/G > T mutations with low MAF (1%) and strong sequence context bias (at CpCpN>CpApN, most frequently CpCpG>CpApG), which is known to arise from arti cial guanine oxidation during sequencing library preparation (18,19); lter 2 removes mtDNA mutations if the mutant-rate and mutant base-quality does not pass binominal test (P > 0.0001) (20,21); lter 3 removes mtDNA mutations if the MAF is smaller than the site-speci c threshold determined by site sequencing depth.…”
Section: Development Of Novel Ltering Criteria For Mtdna Mutation Calmentioning
confidence: 99%
“…To reduce false positive mutations, several ltering strategies has commonly been applied (18). First, we assessed the effect of two ltering strategies previously reported on mtDNA mutation calling.…”
Section: Assessment Of Different Mtdna Mutation Ltering Strategiesmentioning
confidence: 99%
“…Even simply large mtDNA fragments are very rare in the human nuclear genome. There are a few cases of almost full genome NUMTS -one recently detected in a cancer tissue (Yuan et al, 2017), one in a columbine monkey (Wang et al, 2015), but all of them contain at least some deletion. Moreover, NUMTs appear to be rather stable in the nuclear genomes of various species.…”
mentioning
confidence: 99%